2021
DOI: 10.1021/acsaem.1c02773
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Proton Transport Based on a p-i-n Heterostructure Membrane for Low-Temperature Solid Oxide Fuel Cells

Abstract: The p-i-n junction structure has garnered great interest from researchers due to its increased photoactive area and wider space charger region compared with that of the p-n junction. Herein the ultrawide bandgap (∼6.7 eV) semiconductor alumina (Al2O3) has been introduced to construct a p-i-n junction with ZnO and NiO. ZnO–Al2O3–NiO powders are suitable for electrolyte membrane material of low-temperature solid oxide fuel cells (LT-SOFCs). The insulating Al2O3 brings a doubled depletion region and more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…And the O 1s XPS spectra in Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 could be fitted into three peaks at 532.94, 531.61, and 530.82 eV, which are assigned to the lattice oxygen atoms, oxygen atoms neighboring defects and oxygen atoms of the surface. 35,41,42 The ratio O v /O L for Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 was significantly higher than SrZr 4 (PO 4 ) 6 , indicating that there are more oxygen vacancies. The increased amount of deficient oxygen species is ascribed to the doping of Sr 2+ in the sites of Zr 4+ .…”
Section: Structural and Morphological Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…And the O 1s XPS spectra in Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 could be fitted into three peaks at 532.94, 531.61, and 530.82 eV, which are assigned to the lattice oxygen atoms, oxygen atoms neighboring defects and oxygen atoms of the surface. 35,41,42 The ratio O v /O L for Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 was significantly higher than SrZr 4 (PO 4 ) 6 , indicating that there are more oxygen vacancies. The increased amount of deficient oxygen species is ascribed to the doping of Sr 2+ in the sites of Zr 4+ .…”
Section: Structural and Morphological Analysismentioning
confidence: 94%
“…From Figure 1d, it can be seen that the reunion status of Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 is similar to that of SrZr 4 (PO 4 ) 6 . 35 Sr XPS spectrum (Figure S1a of the Supporting Information) of Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 Sr 3d 3/2 and Sr 3d 5/2 exhibit binding energies of 135.44 and 133.48 eV. The binding energies of Sr 3d 3/2 and Sr 3d 5/2 in SrZr 4 (PO 4 ) 6 (Figure S1c) are higher than that of Li 2.5 Sr 0.75 Zr 1.25 (PO 4 ) 3 .…”
Section: Structural and Morphological Analysismentioning
confidence: 99%
“…In recent years, novel symmetrical CFCs using lithium compounds, that is, Ni 0.8 Co 0.15 Al 0.05 LiO 2 (NCAL) as electrodes with a cell configuration of NCAL/electrolyte/NCAL were reported for low temperatures. These fuel cells have intriguing potential toward commercialization because of good performance and high ionic conductivity below 600 °C. Some researchers reported that the high ionic conductivity is attributed to the surface/interface ionic transportation. For example, Xing et al reported that high concentrations of oxygen vacancies in the CeO 2 surface layer promote the proton transportation . Super proton conductivity of 0.16 S cm –1 was achieved in the as-prepared CeO 2 electrolyte at 520 °C, which is much higher than the bulk oxygen ionic conductivity in doped cerium oxide. , However, the electrolyte is porous in these cells because they are fabricated with the dry press method and have not been sintered at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Such specific properties make them good candidates for achieving superior performance at low temperatures. [9,[23][24][25][26] Moreover in recent year, the core-shell heterostructure is typical and raises interest in nanomaterials structure. In the core-shell heterostructure, the interfaces are considered the primary channels for ion conduction.…”
Section: Introductionmentioning
confidence: 99%
“…They are proven to be more feasible electrolyte materials in terms of high ionic conductivity and suppressed electronic conduction. Such specific properties make them good candidates for achieving superior performance at low temperatures [9,23–26] . Moreover in recent year, the core‐shell heterostructure is typical and raises interest in nanomaterials structure.…”
Section: Introductionmentioning
confidence: 99%